2016
DOI: 10.1503/cmaj.160461
|View full text |Cite
|
Sign up to set email alerts
|

Safety of labour and delivery following closures of obstetric services in small community hospitals

Abstract: The safety of obstetric services in small, rural communities remains uncertain. Delivery at hospitals with low delivery volumes has been correlated with better, worse and comparable pregnancy outcomes compared with delivery at larger centres, [1][2][3][4][5][6][7] and studies examining the safety of delivery at rural versus urban hospitals have likewise produced conflicting results. [8][9][10][11][12] Establishing the relative safety of obstetric care in small rural hospitals is challenging. Studies comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Three studies were from the UK, with two reported as abstracts only 15 16 and one an unpublished data series from East Lancashire Hospitals NHS Trust, UK (East Lancashire Hospitals NHS Trust, unpublished data 2017). There appeared to be overlap between populations reported in two studies (East Lancashire Hospitals NHS Trust, unpublished data 2017) and Fleming et al 15 Three studies were from Scandinavia, 7 17 18 three from Canada [19][20][21] and one from France. 5 Seven studies compared adverse birth outcomes before and after centralisation of services, which included closure of varying numbers of OUs.…”
Section: Review Resultsmentioning
confidence: 99%
“…Three studies were from the UK, with two reported as abstracts only 15 16 and one an unpublished data series from East Lancashire Hospitals NHS Trust, UK (East Lancashire Hospitals NHS Trust, unpublished data 2017). There appeared to be overlap between populations reported in two studies (East Lancashire Hospitals NHS Trust, unpublished data 2017) and Fleming et al 15 Three studies were from Scandinavia, 7 17 18 three from Canada [19][20][21] and one from France. 5 Seven studies compared adverse birth outcomes before and after centralisation of services, which included closure of varying numbers of OUs.…”
Section: Review Resultsmentioning
confidence: 99%
“…This approach was used to evaluate how the closure of planned obstetrical services in small hospitals in British Columbia, Canada, affected the labour and delivery outcomes of women residing in affected communities. 9 Ethical approval was granted by the University of British Columbia/BC Children’s and Women’s Hospital Research Ethics Board. For illustrative purposes, we simplify the analysis to a comparison of outcomes of women living in the hospital catchment areas after versus before the closure of services (excluding the control communities used to further account for underlying time trends in the original publication).…”
Section: Methodsmentioning
confidence: 99%
“…We apply the approach to data from our recent study evaluating the safety of labour and delivery following the closure of planned obstetrical services in 21 rural hospitals in British Columbia, Canada. 9 …”
Section: Introductionmentioning
confidence: 99%
“…However, a paradigm shift toward interconnected care is increasingly a reality in practice, driven by the idea that addressing maternal and neonatal health together is pragmatic, cost-effective, and produces better results [7], [8]. In addition, researchers are beginning to use the measurement benefits of composite outcomes with both maternal and neonatal indicators [9], [10], [11], [12]. We support the use of composite outcomes in the maternal and newborn health field, as they circumvent a contrived prioritization of one-half of the mother–infant pair and acknowledge the interconnectedness of mothers and babies at the time of childbirth.…”
mentioning
confidence: 99%
“…In addition, we averaged the causal effects of the three component outcomes such that each outcome held the same statistical weight in the composite. As an alternative, assigning weights to each component is a viable solution that other maternal and neonatal composites have used [10], [11], [12]. In our analyses, maternal morbidity rates were the main driver of positive composite outcome events because this indicator had both the highest prevalence and most variance.…”
mentioning
confidence: 99%